Enhanced reactive oxygen species through direct copper sulfide nanoparticle-doxorubicin complexation. (22nd November 2017) - Li, Yajuan; Cupo, Michela; Guo, Liangran; Scott, Julie; Chen, Yi-Tzai; Yan, Bingfang; Lu, Wei
Abstract: CuS-based nanostructures loading the chemotherapeutic agent doxorubicin (DOX) exerted excellent cancer photothermal chemotherapy under multi-external stimuli. The DOX loading was generally designed through electrostatic interaction or chemical linkers. However, the interaction between DOX molecules and CuS nanoparticles has not been investigated. In this work, we use PEGylated hollow copper sulfide nanoparticles (HCuSNPs) to directly load DOX through the DOX/Cu 2+ chelation process. Distinctively, the synthesized PEG–HCuSNPs–DOX release the DOX/Cu 2+ complexes into surrounding environment, which generate significant reactive oxygen species (ROS) in a controlled manner by near-infrared laser. The CuS nanoparticle-mediated photothermal ablation facilitates the ROS-induced cancer cell killing effect. Our current work reveals a DOX/Cu 2+ -mediated ROS-enhanced cell-killing effect in addition to conventional photothermal chemotherapy through the direct CuS nanoparticle-DOX complexation.